Understanding strategic management - Henry, Antony E. (New York Oxford University Press, 2011)
Building upon the strengths of the first edition, Understanding Strategic Management, Second Edition, features an exceptionally clear writing style that conveys complex information in a clear manner. It also retains the previous edition's use of analysis; relevant, up-to-date case material; and coverage of various perspectives in the field. Numerous real-life examples help to illustrate the core concepts and theory underlying strategic management. With an emphasis on providing students with essential analytical tools, this edition links the text more closely to the Companion Website. The website hosts additional quantitative material, which is signposted throughout the text.
Includes index
Keywords: Strategic Management